A Study of the “Kitab Al-Ghasb” (Book of Violation) from Imam Shams al-Din Muhammad al- Tamartashi’s Moein Al-Mufti - Hammadi, Jamal Ibrahim; Abdel-Ami, Mahmoud Shams El-Din (Journal of Tikrit University for Humanities, 2020)
The research is based on the revival of a manuscript related to the subject of jurisprudence (Al-Ghasb) in the book entitled Kitab al-Ghasb from Moein Al-Mufti of the great scholar (Shams al-Din Muhammad bin Abdullah bin Ahmed bin Muhammad al-Khatib al-Tamartashi al-Ghazi al-Hanafi (d. 1004 AH). There are two copies of the book. The closest copy to the age of the researcher was studied by the researchers, and then a comparison was made between the two copies, showing the gaps between them, checking the spelling according to the modern forms. This paper is divided into three sections and a conclusion.